Erste wissenschafliche Ergebnisse einer Reise nach Afghanistan im Sommer 1963 - Rathjens, Carl (ERDKUNDE, 1964)
In summer 1963 the author, together with his assistent Dr. C. Jentsch, travelled on land from the Middle East to Afghanistan. This paper is a first report of the scientific results. The geomorphology of the Afghan Hindukush was advanced by observations of the snow line and limits of solifluxion, as well as indicators of glaciation during the Würm glacial period and the water regime of the Ab-i-Istada, today with interior drainage only. New material relevant to a tectonic and climatic geomorphology of the country between the high mountains and the desert has been gained. The author was able to visit and study for the first time the woodland areas of Nuristan and Khost, and found particularly interesting the changes in the plant cover due to man. Many observations and investigations were concerned with cultivation, social structure and demography in their ethnical differentiations, especially in the out-of-the-way regions of Hesarajat and Nuristan. Others had the manifold problems of Afghan nomadism as their object. On the basis of these observations some pronouncements can be made on the modern development of Afghanistan which is of particular interest owing to the geographical location of the country vis-a-vis the rest of the Orient.